The Implementation of 15-Minute Extensive Reading Approach As School Literacy Movement Activity: Students' Perceptions - Nizma Nizma; Irene Nany Kusumawardani (Institut Agama Islam Negeri Palopo, 2023)
The low rate of Indonesian students’ literacy skills need to be deliberated more. Responding to this issue, the government created the school literacy movement program to improve Indonesian students’ literacy. The aim of this study is to investigate the implementation as well as the students' perceptions towards 15-minute extensive reading as school literacy movement (GLS) activity in the classroom. This study employed a qualitative method which applied descriptive case study design. The research was conducted at SMP Brawijaya Smart School Malang. The instruments were observation notes and interview guidelines. The interview involved two students who have been undergoing extensive reading activity at school. The collected data were analysed by using interactive analysis model which was carried out in four stages, namely collecting data, data reduction, data display, and conclusion drawing. The findings showed that the implementation of 15-minute extensive reading approach as school literacy movement in SMP Brawijaya Smart School Malang was held quite well by involving and reflecting 9 of the 10 principle of extensive reading as well as two stages of the school literacy program (GLS) namely habituation and development. The findings also revealed that the implementation of 15-minute extensive reading approach as school literacy movement activity is categorically helpful for SMP Brawijaya Smart School Malang students’ literacy and second language acquisition.